Utilization by Escherichia coli of a high-molecular-weight, linear polyphosphate: roles of phosphatases and pore proteins. - Rao, N N (1988)
We observed that wild-type Escherichia coli utilized a linear polyphosphate with a chain length of 100 phosphate residues (poly-P100) as the sole source of phosphate in growth medium. A mutation in the gene phoA of alkaline phosphatase or phoB, the positive regulatory gene, prevented growth in this medium. Since no alkaline phosphatase activity was detected outside the wild-type cells, the periplasmic presence of the enzyme was necessary for the degradation of polyphosphate. A 90% reduction in the activity of periplasmic acid phosphatase with a pH optimum of 2.5 (delta appA mutants) did not affect polyphosphate utilization. Of the porins analyzed (OmpC, OmpF, and PhoE), the phoB-inducible porin PhoE was not essential since its absence did not prevent growth. To study how poly-P100 diffused into the cells, we used high-resolution 31P nuclear magnetic resonance (31P NMR) spectroscopy. The results suggest that poly-P100 entered the periplasm and remained in equilibrium between the periplasm and the medium. When present individually, porins PhoE and OmpF facilitated a higher permeability for poly-P100 than porin OmpC did. The degradation of polyphosphate by intact cells of E. coli observed by 31P NMR showed a time-dependent increase in cellular phosphate and a decrease in polyphosphate concentration.